Stranka u postupku ishođenja građevinske dozvole - Vitez Pandžić, Marijeta (2019)
Ovim se radom analizira ograničavanje pojma i položaja stranke u postupcima ishođenja građevinskih dozvola premaodredbama Zakona o gradnji, a u odnosu na Zakon oopćem upravnom postupku. Premda je Zakon o općem upravnompostupku čl. 3/1. predvidio mogućnost odstupanjaod vlastitih odredbi, odredbama Zakona o gradnji kojimase definira stranka u postupcima ishođenja građevinskihdozvola ide se izvan pretpostavki spomenutog članka. Iakose ova tematika analizirala u hrvatskoj pravnoj teoriji, dodanas nije provedena nikakva inicijativa radi korekcije tihodredaba Zakona o gradnji. Autorica stoga nadograđujeovu tematiku analizirajući pojam i položaj stranke iz izdvojenihizvora upravnog prava Europske unije, relevantnihodredaba Zakona o općem upravnom postupku te sudskeprakse. Nakon provedene teorijske analize, proučavanjemdijela rezultata empirijskog istraživanja utvrđuje se i određena razina neučinkovitosti u provođenju navedenihodredbi Zakona o gradnji.
The paper analyses the specific definition of the term party to the procedure in issuing building permits in compliance with the provisions of the Construction Act. Even though the General Administrative Procedure Act (GAPA) regulates prerequisites for departures from the provisions in special legislation, special regulation of administrative proceedings in accordance with provisions of individual special laws is a departure from, and even contradictory to, the aforementionedprovisions of the GAPA. Such departures have also been observed in several provisions of the Construction Act and this paper analyses them considering the party to the procedure in issuing building permits. Although the GAPA has provided the appropriate regulation of the notion of the party and defined the means which may be applied in the administrative procedure to obtain a building permit, the legislator has opted for special regulation through provisions of the Construction Act, regardless of the fact that justification and purpose of suchspecial regulation is nowhere required or presented. In order to additionally present issues related to relevant regulation of the notion of the party in accordance with the provisions of the Construction Act, the paper reviews regulation of the party in sources of the EU law, in relevant case-law, and within the framework of an empirical research. It emphasises the question of purposefulness of special regulation regarding the notion of the party to the procedure in issuing buildingpermits. In order to test the hypothesis presented in Introduction, the author uses inductive and deductive methods, analysis and synthesis, as well as descriptive statistical methods to interpret some of the results of the empirical research for the purpose of this paper. Grammatical, logical, and teleological interpretation methods are used to interpret the sources of law.
Bibliografske bilješke uz tekst ; bibliografija i izvori: str. 324-326.
Sažetak ; Summary.
Keywords: Zakon o općem upravnom postupku -- Zakon o gradnji; Građevinska dozvola -- Stranke